SYSTEMATIC LITERATURE REVIEW: DAMPAK INVESTASI PENDIDIKAN TERHADAP KEMAJUAN EKONOMI - Andi Adam Rahmanto; Veronica Cynthia Wijayanti; Diya Rofika Rahmawati; Aprilia Nur Arninasari; Mintasih Indriayu (Program Studi PGSD Universitas Flores, 2024)
Investments made in the education sector are an investment strategy that allocates costs for providing education in a country. The aim of preparing this research is to determine the impact of educational investment on a country's economic progress. The method used in this research is a Systematic Literature Review (SLR). This research shows that educational investment has an important role in economic growth, but its impact varies depending on the regional context and the policies implemented. The importance of policy and funding reforms to improve the quality of education is also highlighted, while restrictions on investment in basic scientific inquiry are noted. Appropriate strategies in allocating educational resources are needed to optimize their benefits, especially in less developed areas. This research concludes that education is considered an important strategic investment for the development of human resources and the economic growth of a country. With educational investments ranging from early childhood education to higher education, positive impacts include increased productivity and reduced poverty in the long term.